The role of water and nutrient availability in determining above and below ground allocations in a C4 grass Stipagrotis ciliata desf. de Winter - Moore, Timothy E (Department of Biological Sciences, 2017)
In order to understand the impacts climate change will have on plants it is important to understand the role of functional diversity in determining plant success across a range of environments. Two populations of Stipagrostis ciliata were compared at two sites - drier coastal and wetter inland - that varied in their water and nutrient availability. Analysis indicates an inverse relationship between rainfall and N availability, with the drier coastal site having significantly lower soil and plant δ¹⁵N (Zadi= -1.964, p<0.05). Plant percent N decreased by 63% between the coastal and inland site. Mean root: shoot ratios also differed significantly between sites (Zadi= -1.964, p<0.05). Although total rooting depth did not appear to differ between sites, in total more root material was found per plant at the inland site, with 40% of all root material occurring directly below the plant. At the coastal site, a greater proportion of root material was allocated laterally in the upper 10cm of soil. As expected, water use efficiency, based on δ¹³C, was higher at the drier coastal site. It is proposed that plants will alter above and below- ground allocation depending on the nature of the limiting resource. In dry environments, more root material in upper soil layers, and a faster growth rate associated with higher shoot allocation, may enhance water uptake. Where nutrients are limiting, increased root biomass might increase nutrient, especially N interception. Competition may also be higher at low nutrient sites.